The Importance of Entrepreneurship Education in Physics Education Study Program: Reviewed from Students' Perspectives - Adrian Bagas Damarsha; Dwikoranto Dwikoranto; Muhammad Satriawan; Hanandita Veda Saphira (Mitra Edukasi dan Publikasi, 2025)
The development of the world of education today requires graduates not only to master academic competencies but also to have an entrepreneurial spirit. Therefore, it is necessary to strengthen SDG 4 (Quality Education) in order to create competent human resources in entrepreneurship. In this context, the concept of edupreneurship (a combination of education and entrepreneurship) is becoming increasingly relevant, especially for graduates of the Physics Education study program, who have so far been considered primarily oriented toward conventional academic or industrial careers. This study aims to describe the perspectives and factors resulting from the edupreneur course. The method used is a mixed-methods approach, which combines quantitative and qualitative methods. Data collection techniques are carried out through questionnaires distributed to physics education students. Data analysis used is EFA analysis and thematic qualitative description. The results obtained show that the edupreneur course provides three factors for students, namely AE (Entrepreneurial Action), PE (Entrepreneurial Education), and ME (Entrepreneurial Motivation). The results of student perspectives show that the edupreneurship course is essential to teach. It proves that edupreneurship courses can shape students' entrepreneurial spirit. That is because educational programs also require entrepreneurial skills, starting from idea development. The studies suggest that integrating edupreneurship across academic programs is crucial. By highlighting the importance of entrepreneurship in education, this study recommends that edupreneurship courses be integrated evenly into all study curricula, enabling the realization of SDG 4. That is because the curriculum in Indonesia emphasizes not only academic skills but also entrepreneurial skills.